Philanthropic entrepreneurship: Private donations and knowledge support in Greece - Claire Economidou (SPOUDAI - Journal of Economics and Business, 2017)
The present paper aims to explore the role of philanthropic private donations to knowledge creation in Greek universities and research institutions. Based on survey data and balance sheets of 260 mostly private foundations that finance educational and research activities in Greece, this paper consists the first systematic approach to assessing the impact of Greek philanthropy on fostering human capital development and knowledge creation in Greece. Our analysis shows that private donations are becoming an increasingly important source of revenue. Philanthropy has not substituted for government funding but rather acted as a complement of financing academic research that is too experimental, or too uncertain and therefore shunned by government funding. In an era of stagnant government funding and tight university budgets -mainly due to the 'Greek crisis'- for science programs, large donors are stepping in to help. On average, 15 to 20 million euros -through fellowships and grants- every year and for the last five years are channelled into supporting research and human capital development within Greece as well as into financing the mobility of talented Greek students and academic personnel across EU educational and research institutions.
Keywords: L26; O30; 330; Philanthropic Entrepreneurship; Donations; Knowledge; Institutions; Growth